'Lo humano' y la experiencia mística desde el relato de Etty Hillesum - Navarro Sánchez, Rosana (Veritas, 2016)
In the ambit of the present situation of the crisis of the 'human', as well as of the current outpouring of the mystic phenomenon, this reflection approaches contemporary mystical experience by one of its witnesses: Etty Hillesum. The approach to the narrative of her diary made it possible to say of the "being", which is to say about the human in the mystical experience would open a way through a hermeneutic existential exercise with the mediation of the story. The main issue consisted of searching in the mystical experience, the root and expressions of its humanizing force. In this sense, from an approximation to the 'human' from the categories: interiority, theological attitude and otherness, the reflection opened the way for consideration on the mystical experience and its connection with the 'human' which seeks its humanity. This matter which made it possible to set out some perspectives that contribute to make explicit the humanizing potential of the Mystical Experience today. (English)